Does minimum age of employment regulation reduce child labor? - Eric V. Edmonds (IZA World of Labor, 2014)
Regulation of the minimum age of employment is the dominant tool used to combat child labor globally. If enforced, these regulations can change the types of work in which children participate, but minimum age regulations are not a useful tool to promote education. Despite their nearly universal adoption, recent research for 59 developing countries finds little evidence that these regulations influence child time allocation in a meaningful way. Going forward, coordinating compulsory schooling laws and minimum age of employment regulations may help maximize the joint influence of these regulations on child time allocation, but these regulations should not be the focus of the global fight against child labor.
Keywords: J13; J80; O15; 330; child labor; human capital; social protection